Measuring Students’ Critical Thinking Skills in Human Reproductive System Learning: Validity and Reliability Evidence - Farhani, Nurisma; Sarkity, Dios; Nevrita, Nevrita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Critical thinking has become a fundamental competency in twenty-first-century education and must be carefully cultivated and assessed within biology instruction, particularly in topics related to the human reproductive system. Accordingly, the availability of valid and reliable assessment instruments is essential to ensure accurate measurement of students’ critical thinking skills. This study aimed to develop and evaluate the feasibility of an instrument designed to measure critical thinking in the context of human reproductive system content, with emphasis on empirical validity and reliability. A quantitative approach with a descriptive research design was employed in this study, involving 24 students from class XII.3 at SMA Negeri 6 Tanjungpinang. Data were collected using a test instrument consisting of 12 essay items constructed based on Ennis’s critical thinking indicators. Empirical validity was examined using the product–moment correlation technique, while reliability was determined through Cronbach’s Alpha coefficient with the assistance of SPSS software. The findings revealed that 10 of the 12 items met the criteria for empirical validity, whereas 2 items were deemed invalid. The reliability analysis produced a Cronbach’s Alpha value of 0.799, indicating a high level of internal consistency. These results suggest that the developed instrument is appropriate and dependable for assessing senior high school students’ critical thinking skills on the topic of the human reproductive system.